Quantitative assay of Indole Acetic Acid-producing bacteria isolated from several lakes in East Java, Indonesia - Sulistya Ika Ramadhani Sulistya; Sitoresmi Prabaningtyas Sitoresmi; Agung Witjoro Agung; Rina Triturani Saptawati Rina; Achmad Rodiansyah Achmad (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Ramadhani SI, Prabaningtyas S, Witjoro A, Saptawati TR, Rodiansyah A. 2020. Quantitative assay of Indole Acetic Acid-producing bacteria isolated from several lakes in East Java, Indonesia. Biodiversitas 21: 5448-5454. Biofuel is an alternative to fossil fuels that are environmentally friendly with low emissions. Biofuel from biomass microalgae, especially Chlorella vulgaris, has an essential role in biofuel production. Increasing biomass microalgae was done by co-culture between microalgae and bacteria. This research aims to determine the potential of bacterial isolates to produce the IAA hormone and identify the highest isolate with the ability to synthesis IAA from four lakes in East Java. This research was conducted by culturing bacterial isolates in the Tryptic Soy Broth (TSB) to add tryptophan media in various periods of incubation. The absorbance was measured with UV-Vis spectrophotometry at a wavelength of 530 nm for determining IAA-production from bacterial isolates. The results showed that the "12" code bacterial isolate from Ranu Grati produced the highest IAA hormone concentration, with an average of 30.23 ppm. The morphological characterization of the highest IAA-producing bacteria showed that isolate included the Enterobacteriaceae group and phenotypic characterization include Enterobacter cloacae complex (ECC).